Analisis Implementasi Sistem Pengendalian Internal Dalam Pengelolaan APBD Kota Jambi - Hanifah, Alya; Kusumastuti, Ratih (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2024)
This research is motivated by the need to understand and analyze the government's internal control system in managing Regional Budget funds (APBD) in Jambi City. The main focus of the research is to explain the implementation of the internal control system by the Jambi City Regional Financial and Asset Management Agency (BPKAD) in the context of APBD management. This research uses descriptive qualitative methods, with the primary objective of describing and describing existing phenomena. Through observation, interviews, documentation, and checking the validity of the findings, this research aims first to understand the government's internal control system applied in managing APBD funds in Jambi City. Second, this study aims to analyze the effectiveness of the internal control system implemented by BPKAD Jambi City in managing APBD funds. The results showed that BPKAD Jambi City had successfully implemented the Government's Internal Control System (SPIP) according to the Ministry of Home Affairs guidelines.